(untitled) (Journal of Natural Language and Linguistics, 2024)
This comparative analysis investigates the combinatorial properties of Chinese noun measure words and Arabic classifiers exploring their semantic syntactic and cultural aspects. Chinese measure words are integral to quantifying nouns exhibiting diverse semantic alignments and syntactic patterns. In contrast, Arabic classifiers fulfill a similar role but with distinct structural variations influenced by grammatical gender and number agreement. By juxtaposing these linguistic elements, this study unveils both commonalities and disparities, offering insights into the intricate ways languages encode quantification. Through this comparative examination, we gain a nuanced understanding of linguistic diversity and cultural nuances inherent in Chinese and Arabic, enriching our comprehension of language structure and cross-linguistic communication.